(3QSGdI GdJHjjf hGdGSJOQGc dHYV eGde JOQcI GdYbhd aj cTa GdcaQ GdeMLhH ef GdEdMGO hGdETQGcs - (3MeRI Hf Ydj Hf CMeO GdaGQSqj GdMGcej GdOQRj , J (B433 (3g`s
(3ChdgG (B:s
(3JhcdJ Ydi Gdehdi GdEdg GdMGce eDRd GdCRd hJhSdJ Zdjg Hhdjg GdbGFe GdgGOi YdI GdYdd s
(3BNQgG (B:s
(3hjhVM Cfge NGdahG CeQ GdHGQi hNQLhG Yf Sff GdJhMjO hGdOf dcf Nai Yf Cee GdTQc cdGe GdeYHhO JeJ HMeO Gddg hefg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B70s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ , RNGQa s
Keywords: (3GdJhMjO hGdedd hGdfMds